Evaluation Method of Coal-Bed Methane Fracturing in the Qinshui Basin. (17th March 2020) - Chen, Zhengrong; Sun, Tengfei
Abstract : In order to evaluate the productivity effects of coal-bed methane well fracturing, the relationship between the five factors of horizontal in situ stress difference is analyzed: fracturing friction, net pressure, fracture morphology, fracturing curve shape, and fracturing effect, taking the coal-bed methane wells in the Qinshui Basin as the research target. The results show that the smaller the horizontal in situ stress difference, the larger the fracture stimulation volume; the smaller the fracturing friction and the net pressure, the higher the productivity of the coal-bed methane well; the greater the proportion of coal-bed methane wells with complex fractures in the form of fracturing fractures, the greater the productivity; the fractures formed by descending and mixed fracture curves are ideal, and the effect after fracturing is better. Based on support vector machine for the above five factors, a fracturing effect classification and evaluation model is established using the fractured wells in the target block as training samples, and the effect prediction of nearby coal-bed methane wells is performed. The results show that the prediction results are in excellent agreement, comparing the prediction classification results of support vector machine with the average daily gas production. This theoretical method realizes the classification of the complex effects of coal-bed methane fracturing and provides a theoretical basis for the design of coal-bed methane well production stimulation and effect prediction.